PENGARUH CORPORATE GOVERNANCE DAN KUALITAS PENGUNGKAPAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Sulaiman, Syifa’ Ibnatu; Herwiyanti, Eliada; Kusuma, Poppy Dian Indira; Putri, Negina Kencono (Jurnal Riset Keuangan dan Akuntansi, 2025)
This study aims to examine the impact of corporate governance and disclosure quality on earnings management in manufacturing companies listed on the Indonesia Stock Exchange.  This study utilized samples from 67 manufacturing companies that satisfied the sampling criteria for the purposive sampling method. Multiple linear regression analysis was used to analyze the data, and the results indicated that: (1) Managerial ownership has a positive effect on earnings management; (2) Institutional ownership has no effect on earnings management; (3) The board of directors has no effect on earnings management; (4) The independent commissioner has no effect on earnings management; (5) The audit committee has a negative effect on earnings management; and (6) Disclosure quality has no effect on earnings management.  It has been demonstrated that more audit committees can work more effectively to reduce earnings management practices. From the finding it is also necessary for developing a disclosure structure that will prevent earnings management more effectively is necessary. Keywords: Corporate Governance, Institutional Ownership, Managerial Ownership, Board of Directors, Independent Commissioners.